La pericolosa interpretazione contra constitutionem della giurisprudenza boliviana sui mandati presidenziali (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2019)
There has always been a confusion according to the Bolivian legal doctrine about the real duration of the Presidential office and the possibility of a sine tempore re-election. In April 2013 and in November 2017, the Bolivian Tribunal Constitucional Plurinacional (TCP) struck down any limit on Presidential re-election, in order to preserve the fundamental  right to vote, according to the system of the Interamerican Convention of human rights. In December 2018, even the Tribunal Supremo Electoral (TSE) admitted the re-elegibility of President Morales, being able him to run for the primaries on January 2019. It possibly clears the way to a dangerous contra constitutionem interpretation in contrast with political and democratic stability in the State.